2009
DOI: 10.1111/j.1467-8594.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous Allure: The Value–Pragmatics Model of Ethical Decision Making

Abstract: Research in organizational ethics emphasizes those dispositional factors that are expected to foster positive ethical behavior. We seek to contribute to this literature by including personal values that are in contention with moral outcomes. Specifically, we combine the values of hedonism and power with benevolence and universalism. Our underlying premise of this value-pragmatics model is that nonmoral, as well as moral, dispositional characteristics simultaneously influence ethical decision making. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This type of focus on higher-order values is useful because it allows us to compare whole values systems in relation to an external variable instead of concentrating on single values at an individual level (Schwartz, 1996quoted from Kaldschmidt 2011. This recognizes the fact that opposing values are activated in the face of moral decision making, which can lead to ethical dilemmas (Watson et al 2009). In such cases, a decision will then often be taken based on the importance attributed to any of the relevant competing values (Schwartz 2013).…”
mentioning
confidence: 99%
“…This type of focus on higher-order values is useful because it allows us to compare whole values systems in relation to an external variable instead of concentrating on single values at an individual level (Schwartz, 1996quoted from Kaldschmidt 2011. This recognizes the fact that opposing values are activated in the face of moral decision making, which can lead to ethical dilemmas (Watson et al 2009). In such cases, a decision will then often be taken based on the importance attributed to any of the relevant competing values (Schwartz 2013).…”
mentioning
confidence: 99%
“…Watson et al (2009) found a significant interaction between the quest for pleasure (hedonism), punishment and unethical decisions in the judgment category. In addition, those high in hedonism and with a high value for power were more likely to be influenced to act unethically if the rewards were high.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Moral reasoning is generally understood as a process affected by cognitive reasoning or emotion (Weaver et al, 2014). Moral reasoning is predominantly attributed to gender (Cagle & Baucus, 2006;Eweje & Brunton, 2010), personality (Ruedy & Schweitzer, 2010;Watson et al, 2009), or philosophy/value orientation (Beekun et al, 2008;Fernando & Chowdhury, 2010). In addition, researchers have found that moral reasoning can be influenced by organizational forces (Craft, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, influences on individuals' moral reasoning may be stronger when looking at personal experiences, such as gender, personality or philosophy/value orientation, or organizational influences, such as an organization's ethical culture or rewards or sanctions imposed by an organization (Sweeney et al, 2010;Watson et al, 2009). Therefore, given our lack of support for Hypotheses 2a and 2b, more so than for Hypotheses 1a and 1b, we generally conclude that other individual or organizational forces may be associated with an individual's ethical profile rather than their country's degree of economic freedom.…”
Section: Discussionmentioning
confidence: 99%